Fyn kinase contributes to tyrosine phosphorylation of the GABA(A) receptor γ2 subunit - Jurd, Rachel (2010)
Phosphorylation of GABA(A) receptors is an important mechanism for dynamically modulating inhibitory synaptic function in the mammalian brain. In particular, phosphorylation of tyrosine residues 365 and 367 (Y365/7) within the GABA(A) receptor γ2 subunit negatively regulates the endocytosis of GABA(A) receptors and enhances synaptic inhibition. Here we show that Fyn, a Src family kinase (SFK), interacts with the γ2 subunit in a phosphorylation-dependent manner. Furthermore, we demonstrate that Fyn binds within a region of the γ2 intracellular domain that is centered on residues Y365/7, with the phosphorylation of Y367 being particularly important for mediating this interaction. Tyrosine phosphorylation of the γ2 subunit is significantly reduced in the hippocampus of Fyn knock-out mice, suggesting that Fyn is an important kinase that contributes to the phosphoryation of this subunit in vivo. Tyrosine phosphorylation of the γ2 subunit is not completely abolished in Fyn kinase mice, suggesting that other SFKs, such as Src, also contribute to maintaining and regulating the endogenous phosphorylation level of γ2-containing GABA(A) receptors. In summary, we demonstrate Fyn as one of the SFKs that binds to and phosphorylates the γ2 subunit of the GABA(A) receptor. This has important implications for the regulation of synaptic GABA(A) receptors via signaling pathways that lead to the activation of Fyn kinase.